Reactive Nodular Fibrous Pseudotumor Mimicking Metastatic Tumor After Gastric Cancer Operation: A Case Report and Literature Review - Chen, Junfa; Zhang, Yang; Shi, Lin; Qian, Zhenyuan; Cheng, Aiping; Fu, Liping (Frontiers in Oncology, 2022)
We describe a case of reactive nodular fibrous pseudotumor (RNFP) misdiagnosed as lymph node metastasis after gastric cancer surgery. Additionally, we summarize the clinical and imaging characteristics of RNFP, combined with the literature, to improve the understanding of preoperative diagnosis. Radiological features of RNFP are a homogenous, isodense, solid mass with gradually mild enhancement on multiphasic abdominal computed tomography (CT), and slight 18F-FDG uptake by positron emission tomography/computed tomography (PET/CT). To the best of our knowledge, this is the first report in the English literature of a case of reactive nodular fibrous pseudotumor associated with gastric cancer and its appearance on PET/CT images.